2006
DOI: 10.2495/cr060301
|View full text |Cite
|
Sign up to set email alerts
|

Blocking time reduction for level crossings using the genetic algorithm

Abstract: The blocking time of a level crossing influences traffic on a road that crosses a rail line. The blocking time of a level crossing will be especially long on a heavy traffic rail line. The purpose of this paper is to reduce the blocking time of level crossings by optimising the railroad schedule. We propose an optimal schedule in which the departure time at each station is delayed minutely from the time of the planned schedule. Since there are many trains on a heavy traffic rail line, the number of combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…e optimal schedule was calculated from a genetic algorithm using time delay for each train at each station as a gene value and the closing time as the fitness value. us, the study confirmed the reduction of the railway level crossing blocking time with the changing combinations of the departure time [19]. Moreover, the study concluded that the rail-road waiting time can be reduced through the application of the genetic algorithm on the calculation of the schedule, taking into account the train's location and speed [20].…”
Section: Introductionmentioning
confidence: 54%
“…e optimal schedule was calculated from a genetic algorithm using time delay for each train at each station as a gene value and the closing time as the fitness value. us, the study confirmed the reduction of the railway level crossing blocking time with the changing combinations of the departure time [19]. Moreover, the study concluded that the rail-road waiting time can be reduced through the application of the genetic algorithm on the calculation of the schedule, taking into account the train's location and speed [20].…”
Section: Introductionmentioning
confidence: 54%